PENGGUNAAN BAHASA INDONESIA PADA PAPAN INFORMASI DI RUANG PUBLIK UIN SYARIF HIDAYATULLAH JAKARTA - Endah Lestari Hidayah; Sekar Kurnia Fitri (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
This study aims to describe the use of language in the public space of UIN Syarif Hidayatullah Jakarta. This research will provide a deeper understanding of the types of language used in posters and information boards and identify relevant patterns and trends in language use. The research method used is descriptive qualitative by collecting data through observation and documentation. The results and conclusions of this study indicate that there are errors in the use of language in formal and informal forms on posters and information boards at the Faculty of Tarbiyah and Teacher Training. These errors include errors in spelling, punctuation, use of capital letters, and standard words. Apart from that, banner boards were also found that used good and polite language in a linguistic context, the use of good and correct Indonesian in public spaces complied with linguistic rules related to EYD and standard grammar. Rules regarding the use of Indonesian in public places are also regulated in Law Number 24 of 2009. Therefore, it is important to correct mistakes in the use of Indonesian in public spaces, especially in educational settings such as universities.